Inpatient addiction consultation and post-discharge 30-day acute care utilization. (1st August 2020) - Weinstein, Zoe M.; Cheng, Debbie M.; D'Amico, Maria J.; Forman, Leah S.; Regan, Danny; Yurkovic, Alexandra; Samet, Jeffrey H.; Walley, Alexander Y.
Highlights: Acute care utilization is common among patients with substance use disorders. No significant association between addiction consults and 30-day care utilization. Impact of medication for opioid use disorder on healthcare utilization merits further study. Abstract: Background: Addiction Consult Services care for hospitalized patients with substance use disorders (SUD), who frequently utilize costly medical services. This study evaluates whether an addiction consult is associated with 30-day acute care utilization. Methods: This was a retrospective cohort study of 3905 inpatients with SUD. Acute care utilization was defined as any emergency department visit or re-hospitalization within 30 days of discharge. Inverse probability of treatment weighted generalized estimating equations logistic regression models were used to evaluate the relationship between receipt of an addiction consult and 30-day acute care utilization. Exploratory subgroup analyses were performed to describe whether this association differed by type of SUD and discharge on medication for addiction treatment. Results: The 30-day acute care utilization rate was 39.5 % among patients with a consult and 36.0 % among those without. Addiction consults were not significantly associated with care utilization (Adjusted Odds Ratio 1.02; 0.82, 1.28). No significant differences were detected in subgroup analyses; however, the decreased odds among patients with OUD given medication was clinically notable (AOR 0.69; 0.47, 1.02). Discussion: Repeat acute care utilization is common among hospitalized patients with SUD, particularly those seen by the addiction consult services. While this study did not detect a significant association between addiction consults and 30-day acute care utilization, this relationship merits further evaluation using prospective studies, controlling for key confounders and with a focus on the impact of medications for opioid use disorder.